Վազգէն Շուշանեանի նամակները Սիմոն Վրացեանին (1927-31) - Մատթէոսեան, Վարդան (տպ. Atlas)
Two members of the Armenian Revolutionary Federation, French Armenian writer Vazken Shushanian (1903-1941) and Simon Vratzian (1882-1969), last prime minister of the first independent Republic of Armenia, corresponded actively in the period 1927-1931. Only a set of 21 letters written by Shushanian has reached us, along with Vratzian’s response to a questionnaire submitted by him. The letters are kept in the archives of the Hamazkayin Cultural Society in Beirut. The letters, which are published with a detailed introduction and endnotes, offer interesting glimpses about literary and political views, as well as Shushanian’s personal struggle to make ends meet while finishing his studies. The letters also offer many details about the early activities of both correspondents on behalf of the Society of Friends of Martyred Writers, founded in 1929 to undertake the publication of the works, both unpublished and/or scattered in the press, of writers murdered during the Armenian genocide.
Keywords: Հրապարակումներ; Նամակագրութիւն